Analysis of Inclusive Education Based on Local Wisdom in a Global Perspective: Factors of Implementation and Integration: A Systematic Literature Review - Sugiarti Sugiarti; Islawati Islawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze inclusive education based on local wisdom from a global perspective, particularly focusing on conceptual development, implementation factors, and forms of integration within educational systems. The research employed a Systematic Literature Review (SLR) using the PRISMA approach by searching the Scopus database within the 2015–2025 period using keywords related to culturally responsive and community-based inclusive education. From 33 identified articles, 13 met the inclusion criteria and were analyzed using thematic analysis. The findings indicate that inclusive education has evolved from an access-oriented approach to a more holistic and contextual framework. The main factors influencing implementation include pedagogical, social, cultural, leadership, and policy aspects. Furthermore, the integration of local wisdom into curriculum design, teaching practices, and community participation enhances the relevance, quality, and sustainability of educational systems. This study concludes that inclusive education based on local wisdom represents a strategic approach to addressing global educational challenges while preserving local cultural identity.